Depth-resolved phase imaging - Jonathan Huntley; Pablo Ruiz (2012)
Traditional full-field interferometric techniques (speckle, moiré, holography etc) encode the surface deformation state of the object under test in the form of 2-D phase images. Over the past 10 years, a family of related techniques (Wavelength Scanning Interferometry, Phase Contrast Spectral Optical Coherence Tomography (OCT), Tilt Scanning Interferometry and Hyperspectral Interferometry) has emerged that allows one to measure the volume deformation state within weakly-scattering objects. The techniques can be thought of as combining the phase-sensing capabilities of Phase Shifting Interferometry and the depth-sensing capabilities of OCT. This paper provides an overview of the techniques, and describes a theoretical framework based on the Ewald sphere construction that allows key parameters such as depth resolution and displacement sensitivity to be calculated straightforwardly for any given optical geometry and wavelength scan range. Finally, the related issue of robust phase unwrapping of noisy 3-D wrapped phase volumes is also described.